Rehearsing Beginning - Sjoerd Westbroek (Revista Portuguesa de Pedagogia, 2022)
In this article I propose to study the education of art educators through the lens of beginning –beginning not as something one does once, but as constitutive of a teacher's practice. Similar to how an artist works in a process-based manner, teaching is an embodied practice developed through repetition, which allows one to shape an individual way of being and doing things. My aim is to develop a language that emphasises a common ground for both art and education, revolving around both being an open-ended process. Investigating the concept of beginning in a practice-based manner, I want to show how art education can become what Freire calls a cognisable object, allowing students to become student-teachers and teachers to become teacher-students, who take turns in testing out new practices.